2008
DOI: 10.1243/09544062jmes655
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of the aerodynamics of spinning and stationary footballs

Abstract: The accurate discrimination of the aerodynamic parameters affecting the flight of sports balls is essential in the product development process. Aerodynamic studies reported to date have been limited, primarily because of the inherent difficulty of making accurate measurements on a moving or spinning ball. Manufacturers therefore generally rely on field trials to determine ball performance, but the approach is time-consuming and subject to considerable variability. The current paper describes the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 17 publications
(29 reference statements)
5
58
1
2
Order By: Relevance
“…A comprehensive experimental study of the forces that are generated specifically on footballs can be found in Passmore 6,7 ; drag and lateral force characteristics are reported for spinning and static balls and in the static case the lateral forces are shown to be a function of orientation. Typical Drag coefficient against Reynolds number for a range of footballs is shown in figure 1 along with the results from Achenbach 2 .…”
Section: Figure 1 Drag Coefficients Against Reynolds Number For a Ranmentioning
confidence: 99%
“…A comprehensive experimental study of the forces that are generated specifically on footballs can be found in Passmore 6,7 ; drag and lateral force characteristics are reported for spinning and static balls and in the static case the lateral forces are shown to be a function of orientation. Typical Drag coefficient against Reynolds number for a range of footballs is shown in figure 1 along with the results from Achenbach 2 .…”
Section: Figure 1 Drag Coefficients Against Reynolds Number For a Ranmentioning
confidence: 99%
“…The methods used to derive the data in Figure 12 were based on those reported by Passmore (2), where the ball is tested across a matrix of fixed wind and spin speeds. This is very time consuming to perform and analyse so the spin method has been modified to improve productivity by running at a fixed spin speed while the tunnel speed is reduced from a maximum of 30 ms -1 down to 10 ms -1 .…”
Section: Figure 12 Lateral Coefficients Against Spin Ratio For Fixed mentioning
confidence: 99%
“…This is generally known as the Magnus effect. Given that the player deliberately applies the spin to the ball and the ball will then fly in the same manner every time, this is a predictable effect, however Passmore (2) shows that the degree of swerve in the ball may differ depending on the ball design.…”
Section: Introductionmentioning
confidence: 99%
“…La Figura 1.11 muestra el túnel con el soporte para las pelotas. El trabajo de Passmore y otros [PTSJ08] con balones de fútbol emplea un túnel de viento de circuito abierto con una sección de 1, 32 × 1,9 m que permite una velocidad máxima de 45 m/s. La medida de las fuerzas se realiza mediante una balanza de 6 ejes de alta precisión diseñada para aplicaciones aeronaúticas permitiendo una resolución de ±0, 012N para arrastre y ±0, 021N para fuerzas laterales.…”
Section: Revisión De Los Trabajos Previosunclassified
“…La obtención de estos parámetros, para el caso de balones de fútbol, se realiza mediante deferentes técnicas, como ensayos en túneles de viento [ASKS07,PTSJ08] Las Figuras 2.13 y 2.14 muestran los resultados obtenidos en los casos de lanzamientos con rotación y sin rotación respectivamente.…”
Section: Particularización Para Balones De Fútbolunclassified